2021
DOI: 10.1126/sciadv.abf1173
|View full text |Cite
|
Sign up to set email alerts
|

Simplifying inverse materials design problems for fixed lattices with alchemical chirality

Abstract: Brute-force compute campaigns relying on demanding ab initio calculations routinely search for previously unknown materials in chemical compound space (CCS), the vast set of all conceivable stable combinations of elements and structural configurations. Here, we demonstrate that four-dimensional chirality arising from antisymmetry of alchemical perturbations dissects CCS and defines approximate ranks, which reduce its formal dimensionality and break down its combinatorial scaling. The resulting “alchemical” ena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 84 publications
3
12
0
Order By: Relevance
“…In Figure 1 (a), clear steps can be observed since all odd orders to not contribute to the final accuracy. This is due to the symmetry [2,8] of the system and can also be observed for the case of N 2 → CO in panel (b) of the same figure. Since this behaviour is a consequence of the symmetry of the perturbation, this step-wise convergence is a necessary criterion for numerical stability.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…In Figure 1 (a), clear steps can be observed since all odd orders to not contribute to the final accuracy. This is due to the symmetry [2,8] of the system and can also be observed for the case of N 2 → CO in panel (b) of the same figure. Since this behaviour is a consequence of the symmetry of the perturbation, this step-wise convergence is a necessary criterion for numerical stability.…”
Section: Resultssupporting
confidence: 72%
“…While some formulations even allow for a change in numbers of electrons [6,7], this work considers isoelectronic changes only. * guido.vonrudorff@univie.ac.at Even though these pen-and-paper formulations already allow for fundamental insights such as quasisymmetries [8] in chemical space or tests of the nearsightedness of the electron density [9], the underlying assumption-the convergence of the Taylor series-has only been postulated and motivated. Numerical tests so far are limited by the numerical accuracy and the finite number of expansion terms that could be calculated.…”
Section: Introductionmentioning
confidence: 99%
“…86,87 We note, however, that these trends change upon removal of the nuclear repulsion terms which do not affect the electronics. The predicted energy ordering is the same, both for the vertical and the relaxed energies, the relaxation calculated only with the first order alchemical force is in fact not able to discriminate alchemical enantiomers 88 and does not change the energy order.…”
Section: B-n Doping Of Benzenementioning
confidence: 63%
“…For this endeavor to be successful, it was necessary to improve on the representation of chemical structures [ 314 , 315 ] and desired properties [ 316 ]. It was also shown that the new concept of alchemical chirality [ 317 ] might allow one to draw direct energy relations across the chemical compound space to accelerate design processes.…”
Section: Conceptual Considerationsmentioning
confidence: 99%